PENERAPAN PEMBELAJARAN DARING DENGAN MODEL PROBLEM BASED LEARNING MELALUI LMS NESABASIAPEL UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS 7 DI SMP NEGERI 1 BATU - Sari, Nila Puspita (CV Sintesia, 2024)
This classroom action research aims to determine whether the application of online learning with the Problem Based Learning (PBL) model through the Nesabasiapel LMS can improve the critical thinking skills of 7th grade students of SMP Negeri 1 Batu on the material of Natural Resources Potential. The research was carried out in two cycles, each cycle consisting of the stages of planning, implementation, observation and evaluation, and reflection. The research subjects were students of class 7G in the first semester of the 2021/2022 academic year, totaling 30 people. The object of research is students' critical thinking skills. The results obtained in this study are the application of the Problem Based Learning model to improve students' critical thinking skills. The results of the observation of students' critical thinking skills showed an increase from cycle I to cycle II, from 70.83% in the first cycle to 82.53% in the second cycle. Based on the results of the study, it can be concluded that the application of the Problem Based Learning (PBL) learning model can improve students' critical thinking skills.